2002
DOI: 10.1140/epje/i2002-10063-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure of colloidal complexes obtained from neutral/poly- electrolyte copolymers and oppositely charged surfactants

Abstract: We report on the phase behavior and scattering properties of colloidal complexes made from block copolymers and surfactants. The copolymer is poly(sodium acrylate)-b-poly(acrylamide), hereafter abbreviated as PANa-PAM, with molecular weight 5000 g/mol for the first block and 30000 g/mol for the second. In aqueous solutions and neutral pH, poly(sodium acrylate) is a weak polyelectrolyte, whereas poly(acrylamide) is neutral and in good-solvent conditions. The surfactant is dodecyltrimethylammonium bromide (DTAB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
200
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(224 citation statements)
references
References 0 publications
18
200
2
4
Order By: Relevance
“…4 quantitatively, we assume for the nanoparticlepolymer complexes a core-shell structure similar to the one found with surfactant micelles [13,15]. In this model, the core is a dense assembly of particles, which dominates the scattering intensity in the wave-vector range of interest (q > 0.01 Å -1 ).…”
Section: Determination Of the Aggregation Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…4 quantitatively, we assume for the nanoparticlepolymer complexes a core-shell structure similar to the one found with surfactant micelles [13,15]. In this model, the core is a dense assembly of particles, which dominates the scattering intensity in the wave-vector range of interest (q > 0.01 Å -1 ).…”
Section: Determination Of the Aggregation Numbersmentioning
confidence: 99%
“…%). The arrow indicates the position of the correlation peak arising from particles interactions located in the cores [13,15]. …”
Section: Determination Of the Aggregation Numbersmentioning
confidence: 99%
“…The two systems are very similar in terms of molecular weights and structures but they differ by their electrostatic charge. For charged-neutral diblocks and surfactants with opposite charges, we have established the thermodynamical phase diagrams and found broad regions where hierarchical aggregates spontaneously form via electrostatic selfassembly [34][35][36][37][38][39][40] . These aggregates are termed colloidal complexes because they form through complexation and because of their colloidal nature 21,41 .…”
mentioning
confidence: 99%
“…More subtle effects seen for protein binding [7] were attributed to charge heterogeneity, which introduces repulsive forces between polyanions and protein negative domains and also alters the nature of the polyanion-binding site. Complexes involving polyelectrolyte-neutral block copolymers and oppositely charged micelles were recently investigated by Berret [8][9][10][11][12]. The structure of such complexes was elucidated by small-angle neutron scattering and it was found that these complexes exhibit a core-shell microstructure, where the core is a dense coacervate microphase of micelles surrounded by neutral blocks.…”
Section: Experimental Investigationsmentioning
confidence: 99%